Electrochemical Interfacial Polymerization toward Ultrathin COF Membranes for Brine Desalination. Issue 13 (17th February 2023) - Wang, Meidi; Wang, Yutong; Zhao, Junyi; Zou, Jiyu; Liang, Xu; Zhu, Ziting; Zhu, Jiashi; Wang, Hongjian; Wang, Yuhan; Pan, Fusheng; Jiang, Zhongyi
Abstract: Ultrathin covalent organic framework (COF) membranes are urgently demanded in molecular/ionic separations. Herein, we reported an electrochemical interfacial polymerization strategy to fabricate ultrathin COF membranes with thickness of 85 nm, by actively manipulate self‐healing effect and self‐inhibiting effect. The resulting COF membrane exhibited superior performance in brine desalination with the permeation flux of 92 kg m −2 h −1 and the rejection of 99.96 %. Our electrochemical interfacial polymerization strategy enriches the fabrication approach of COF membranes and facilitates the rational design of ultrathin membranes. Abstract : An electrochemical interfacial polymerization strategy, which actively manipulates the self‐healing effect and self‐inhibiting effect during electrochemical process, is developed for fabricating ultrathin and robust COF membranes for efficient brine desalination.